Análise da competitividade dos clusters calçadistas do estado de São Paulo - um estudo multicaso. - Milaneze, Kleber Luiz Nardoto (Universidade Federal de São Carlos, 2005)
In the end of the decade of 90, was verified the international adoption of strategies having aimed growth of the exportations and the supported development of the place, with this, governments, industries, suppliers, institutions of P&D and CT&I, class representatives, etc. they had started to search a bigger integration to get competitive advantages of this proximity, from there, it had the appearance clusters in Brazil. This work looked for to study shoes clusters of the State of São Paulo and how its agents are organizing for the construction and consolidation of competitive cluster. The methodology used in this research was qualitative, and it gaves through the use of the case study method. In the development of this study, the factors and subfactors of competitiveness had been analyzed, and the importance of each one of them have in the competitiveness of cluster was observed, as well as its level of implementation according to perception of each one of the searched agents. The level of participation of each one of the agents in clusters involved varies of city for city, and each cluster it prioritizes definitive factors in the search of a bigger competitiveness for the shoes sector of its city.
Keywords: Planejamento estratégico; Indústria do calçado; Cluster; Competitividade; Shoes Sector; Cluster; Competitiveness; Factors and subfactors of competitiveness; ENGENHARIAS::ENGENHARIA DE PRODUCAO